2021
DOI: 10.1074/jbc.ra120.016485
|View full text |Cite
|
Sign up to set email alerts
|

Proteasome subunit α4s is essential for formation of spermatoproteasomes and histone degradation during meiotic DNA repair in spermatocytes

Abstract: Meiosis, which produces haploid progeny, is critical to ensuring both faithful genome transmission and genetic diversity. Proteasomes play critical roles at various stages of spermatogenesis, including meiosis, but the underlying mechanisms remain unclear. The atypical proteasomes, which contain the activator PA200, catalyze the acetylation-dependent degradation of the core histones in elongated spermatids and DNA repair in somatic cells. We show here that the testis-specific proteasome subunit α4s/PSMA8 is es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 49 publications
3
16
1
2
Order By: Relevance
“…Here, increase in proteasome bound PA200 appears to be mainly the consequence of increased expression ( Supplementary Fig. S9 ), which is in accordance with the existing literature (Zhang et al ., 2021). However, given that we did not observe increased binding of PA200 to s20S in the whole testis interactome analysis, it remains difficult to draw conclusions about specific PA200 interactions.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Here, increase in proteasome bound PA200 appears to be mainly the consequence of increased expression ( Supplementary Fig. S9 ), which is in accordance with the existing literature (Zhang et al ., 2021). However, given that we did not observe increased binding of PA200 to s20S in the whole testis interactome analysis, it remains difficult to draw conclusions about specific PA200 interactions.…”
Section: Resultssupporting
confidence: 92%
“…This agrees with the increased proteolytic activities in SPC and SPT, compared to SPG and SER, and similar previous observations using whole testis lysate compared to muscle tissue (Qian et al ., 2013). Another study also showed high levels of 19S-containing species in post-meiotic germ cells (Gomez-H et al ., 2019) and in whole testes (Qian et al ., 2013; Zhang et al ., 2021). The increased association between s20S and activators during spermatogenesis is aligned with increased proteolytic requirements of this process.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…La particule a4s typique du spermatoprotéasome (Figure 3), contrairement à la particule a4, favoriserait l'association au PA200. Elle permettrait aussi le recrutement des sous-unités b1, b2 et b5 plutôt que celles de l'immunoprotéasome (Zhang et al, 2021). Le complexe ainsi formé est essentiel pour la réparation de l'ADN en métaphase I, la progression de la méiose et la fertilité masculine en favorisant, au moins partiellement, la dégradation des histones.…”
Section: Architecture Hiérarchisée Et Propriétés Uniques Des Protéasomesunclassified
“…La signification des différences de composition des protéasomes 26S dans les cellules demeure à ce jour largement incomprise. Les protéasomes atypiques qui contiennent à la fois la particule régulatrice PA200 et la sous-unité a4s, jouent un rôle important dans la fertilité masculine (Zhang et al, 2021). Par ailleurs, dans des neurones cultivés d'hippocampe, la cryo-EM montre que 80 % des molécules de protéasome 26S se trouvent dans la forme appelée parfois « inactive », c'est-àdire sans substrat lié (Asano et al, 2015).…”
Section: Hétérogénéité Des éDifices Moléculaires Des Protéasomes Dans Les Cellulesunclassified